FOLLICULAR CYSTS AND KERATOCYSTS: MODERN APPROACHES TO DIAGNOSIS AND TREATMENT (American Journal of Interdisciplinary Research and Development, 2025)
The article extensively discusses the etiology, clinical signs, diagnostic methods, and modern approaches to treatment of follicular cysts and keratocysts, among odontogenic cysts encountered in maxillofacial surgery. Follicular cysts are usually benign and rarely recur, while keratocysts are characterized by aggressive growth and high recurrence rates. Methods such as curettage and resection are used in surgical practice. Modern technologies — CBCT, laser, endoscopic surgery, cryotherapy, and the use of biomaterials — play an important role in increasing the effectiveness of treatment.